2006
DOI: 10.1108/02683940610673960
|View full text |Cite
|
Sign up to set email alerts
|

The effect of personality on perceptions of justice

Abstract: Purpose -The purpose of this study is to examine the effect that work locus of control has on perceptions of trust, perceived organizational support, procedural justice and interactional justice. Design/methodology/approach -Survey data were collected from 679 alumni of a university in the Southwestern USA. Regression analyses and structural equation modeling were used to test a series of hypotheses. Findings -The results indicate that work locus of control has a significant positive relationship on all variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 49 publications
2
25
0
1
Order By: Relevance
“…First, the findings support and extend emerging evidence concerning the role of individual differences in predicting organizational justice perceptions (e.g., De Cremer and Sedikides, 2005;Lilly and Virick, 2006). Our research confirms that the attachment orientations individuals bring with them to the workplace are associated with interpersonal justice perceptions and the strength of this association may vary depending on national culture.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…First, the findings support and extend emerging evidence concerning the role of individual differences in predicting organizational justice perceptions (e.g., De Cremer and Sedikides, 2005;Lilly and Virick, 2006). Our research confirms that the attachment orientations individuals bring with them to the workplace are associated with interpersonal justice perceptions and the strength of this association may vary depending on national culture.…”
Section: Discussionsupporting
confidence: 77%
“…Our study also supports the hitherto limited research which has demonstrated connections between individual differences in personality (e.g. Big 5, locus of control) and organizational justice perceptions (e.g., Lilly and Virick, 2006;Shi et al, 2009). …”
Section: Discussionsupporting
confidence: 76%
“…Past research has identified the impact of personality in perceptions of justice (e.g. Colquitt et al, 2006;Lilly & Virick, 2006), and specifically in the context of change (Brennan & Skarlicki, 2004;Moon et al, 2008). Elsewhere in our interviews in the broader study of emotions and change, respondents made comments about various experiences of fairness and unfairness and how they triggered affective responses.…”
Section: Limitations Of Research Study and Future Directionsmentioning
confidence: 99%
“…Brennan and Skarlicki (2004) found that angry hostility moderated survivors' perceptions of the fairness of downsizing. Organizational justice perceptions have also been related to other aspects of personality, such as trust propensity, risk aversion, morality (Colquitt, Scott, Judge & Shaw, 2006) and locus of control (Lilly & Virick, 2006), but seldom in the context of change. Pragmatism, which is a hallmark of the Myers-Briggs model (Myers Briggs, Kirby & Myers et al, 1998), persuades people that they need to make the most of whatever occurs, but does not seem to have been empirically investigated in the context of change.…”
Section: Personality Affect and Organizational Changementioning
confidence: 99%
See 1 more Smart Citation